Loliolide - the most ubiquitous lactone - Grabarczyk, Małgorzata; Wińska, Katarzyna; Mączka, Wanda; Potaniec, Bartłomiej; Anioł, Mirosław (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2015)
The searching for biologically active compounds produced by living organisms led to the discovery of a number of compounds with more or less complicated structure. One of the simplest molecules are monoterpenoid lactones and loliolide is the most common among them. Loliolide was found in animals (insects) and plants (flowers, shrubs, trees) both terrestrial and marine, such as algae and corals. Many years of research on plants used in traditional folk medicine of different countries have led to the conclusion that this compound has a variety of biological properties such as anti-cancer, antibacterial, antifungal and antioxidant ones. Moreover, plants containing loliolide are used in alternative medicine in treatment of diabetes and depression. It is extremely interesting that this lactone also affects the behavior of ants as well as the development of certain plants (allelopathic activity). However, sometimes there are side effects as in the case of structural analogues of loliolide contributing to extinction of tropical coral.